2007
DOI: 10.1186/1748-5908-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of care through routine, successful implementation of evidence-based practice at the bedside: an organizational case study protocol using the Pettigrew and Whipp model of strategic change

Abstract: BackgroundEvidence-based practice (EBP) is an expected approach to improving the quality of patient care and service delivery in health care systems internationally that is yet to be realized. Given the current evidence-practice gap, numerous authors describe barriers to achieving EBP. One recurrently identified barrier is the setting or context of practice, which is likewise cited as a potential part of the solution to the gap. The purpose of this study is to identify key contextual elements and related strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 46 publications
3
86
0
Order By: Relevance
“…Thus given the above observations and together with the importance placed on engagement and retention, the high variability in the cognitive, emotional, social and developmental domains [4] differences in roles (e.g. teenagers who are also parents) and levels of autonomy as well as high degrees of dual diagnosis or co-morbidities found in this group [29,30] practitioners are encouraged to also develop competencies in allied psychological treatment models such as Motivational Interviewing [31]; familiarity with the core principles of CBT, disorder specific and problem-specific CBT competences, the generic and meta-competences of CBT as well as an advanced knowledge and understanding of mental health problems that will provide practitioners with the confidence and capacity to implement treatment models in a more flexible yet coherent manner,.…”
Section: Recommendations To Clinicians and Studentsmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus given the above observations and together with the importance placed on engagement and retention, the high variability in the cognitive, emotional, social and developmental domains [4] differences in roles (e.g. teenagers who are also parents) and levels of autonomy as well as high degrees of dual diagnosis or co-morbidities found in this group [29,30] practitioners are encouraged to also develop competencies in allied psychological treatment models such as Motivational Interviewing [31]; familiarity with the core principles of CBT, disorder specific and problem-specific CBT competences, the generic and meta-competences of CBT as well as an advanced knowledge and understanding of mental health problems that will provide practitioners with the confidence and capacity to implement treatment models in a more flexible yet coherent manner,.…”
Section: Recommendations To Clinicians and Studentsmentioning
confidence: 93%
“…Evidence for the clinical application of cognitive behavioural therapy (CBT) for substance use disorders has grown significantly [3][4][5][6][7][8]. Moreover, CBT for substance use disorders has demonstrated efficacy both as a monotherapy and as part of combination treatment [7].…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Evidence-based practice (EBP) is an approach expected to improve the quality of patient care and service delivery in health care systems. Based on Stetler, Ritchie, Rycroft-Malone, Schultz, and Charn's finding [20], the most influential EBP leaders were of long-standing tenure at the time of the site visit and have been present from the start or before the initiative, have been visibly progressing, and possess a continuing and deep commitment to EBP. The results of the study by Stetler et al [20] were also consistent with qualitative findings that indicated that the role model site's leadership, culture, and related staff attitudes were more developed regarding the support of EBP [20].…”
Section: A Citation Analysismentioning
confidence: 99%
“…The nursing profession has long recognized the importance of research as an essential basis for its development [3,48] and has concerned itself with research utilization since the mid 1980s [49] . Research utilization is defined as the use of research to guide clinical practice [50] , and as the transfer of specific research-based knowledge into practice, whether it is used at the bedside, in clinical teaching [7] , or while providing direct patient care, as intended with the intraoperative caring model.…”
Section: Conceptual Use Of the Intraoperative Caring Modelmentioning
confidence: 99%